How Do The Level Of Experience And Coaching Style Affect The Leadership Quality Of KUD Directors In Increasing Business Productivity - Noviardi Ferzi (Balitbangda Provinsi Jambi, 2022)
Level of Experience and Coaching Style on the Quality of the KUD director's leadership affects the village business productivity. This study took 123 respondents who were directors of village businesses. The research approach uses an explanative method using Partial Least Square (SmartPLS 3.0). The research findings show that: (1) the level of experience of directors has a strong and significant effect on the Quality of Leadership with Partial Mediation of the Coaching Style; (2) The level of experience of KUD directors has a strong and significant effect on the Coaching Style performed by the directors; (3) Coaching Style performed by influential directors strong and significant towards the Quality of Leadership; (4) Level The experience of directors has a strong and significant effect on productivity Business with Partial Mediation of Coaching Style and Quality Good leadership from the board of directors; (5) The coaching style performed by the directors has a strong and significant effect on business productivity with Partial Mediation of good Leadership Qualities from the board of directors; (6) Good leadership qualities from the board of directors have a strong and significant effect to the productivity of business.